Rancangan UI/UX Aplikasi Analytics Pada Toko Online Wao.Sneakers Menggunakan Aplikasi Figma - Avindra, Andre; Cahyani, Chentia Metta; Ningsih, Linda Ratu (Fakultas Komputer - Universitas Universal, 2021)
Instagram social media is used by wao.sneakers as a medium to market products and aims to make it easier for consumers or potential buyers to find information about the product to be purchased and also aims to facilitate transactions. Product posts and follower count, is one indicator that can affect the trust and buying interest of a consumer. The purpose of this research is to design a attractive, easy to use and modern UI/UX for an analytics application for wao.sneakers. So that it can increase engagement which has an impact on increase the trust and buying interest of a consumer. The data needed in designing the UI/UX design is obtained by conducting interviews directly with the owner, namely Chathrine. In designing this UI/UX, the editing software used is Figma. With this research is expected to facilitate wao.sneakers in designing a mobile-based analytics application.